Acute necrotizing pancreatitis in a pregnant female diagnosed after caesarian delivery: a case report - Acharya, Foram P.; Mukim, Aditya A.; Acharya, Prashant V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Acute pancreatitis (AP) is a rare event in pregnancy, occurring in approximately 3 in 10,000 pregnancies. The spectrum of AP in pregnancy ranges from mild pancreatitis to serious pancreatitis associated with necrosis, abscesses, pseudocysts and multiple organ dysfunction syndromes. A 21 years old, primigravida presented to labour room at 33 weeks 2 days of gestation with complaint of abdominal pain. Per vulval finding showed pin-point vagina. (patient had history of transverse vaginal septum, and was operated for the same before conception). Patient was operated for caesarian delivery and Fenton’s repair done. Contrast-enhanced computed tomography showed signs of acute necrotizing pancreatitis with peripancreatic collection. AP in pregnancy remains a challenging clinical problem to manage. The general management of AP in pregnancy is supportive.